Authors Make Case for Engaged Scholarship in Social Work Research Methods Guide - Kala Chakradhar (The University of Alabama, 2022)
Review of the book: Qualitative Methods for Practice Research (Pocket Guides to Social Work Research Methods). Jeffrey Longhofer, Jerry Floersch, and Janet Hoy. New York: Oxford University Press, 2012, 216 pages. ISBN 9780195398472.